Soil erosion fragility assessment using an impact model and geographic information system - Jorge, Luiz Alberto Blanco [UNESP] (FapUNIFESP (SciELO), 2009)
A study was taken in a 1566 ha watershed situated in the Capivara River basin, municipality of Botucatu, São Paulo State, Brazil. This environment is fragile and can be subjected to different forms of negative impacts, among them soil erosion by water. The main objective of the research was to develop a methodology for the assessment of soil erosion fragility at the various different watershed positions, using the geographic information system ILWIS version 3.3 for Windows. An impact model was created to generate the soil's erosion fragility plan, based on four indicators of fragility to water erosion: land use and cover, slope, percentage of soil fine sand and accumulated water flow. Thematic plans were generated in a geographic information system (GIS) environment. First, all the variables, except land use and cover, were described by continuous numerical plans in a raster structure. The land use and cover plan was also represented by numerical values associated with the weights attributed to each class, starting from a pairwise comparison matrix and using the analytical hierarchy process. A final field check was done to record evidence of erosive processes in the areas indicated as presenting the highest levels of fragility, i.e., sites with steep slopes, high percentage of soil fine sand, tendency to accumulate surface water flow, and sites of pastureland. The methodology used in the environmental problems diagnosis of the study area can be employed at places with similar relief, soil and climatic conditions.
Avaliação da fragilidade à erosão do solo por meio de um modelo de impacto e sistema de informações geográficas
Keywords: Analytical hierarchy process; Hydric erosion; Water flow